Sinergi Program Bantuan Rumah Tidak Layak Huni di Kabupaten Tanah Datar antara BAZNAS Kabupaten Tanah Datar dengan Pemerintah Kabupaten Tanah Datar - Widi Nopiardo; Asrida Asrida (ZAWA: Management of Zakat and Waqf Journal, 2023)
The problem of poverty certainly cannot be left entirely to the Regional Government to solve it. Ideally, good synergy is needed to solve various problems in the field. Reflecting on the phenomenon of increasing the percentage of post-Covid poverty in Tanah Datar Regency from 15,340 people in 2020 to 15,890 people in 2021 or an increase of 3.59%. BAZNAS Tanah Datar Regency also experienced a decline in zakat collection and distribution. In terms of zakat distribution, there was a decrease from 2021 to 2022 amounting to Rp. 981,623,300,- or 8.46%. This requires synergy to be established, so that poverty alleviation programs can continue to be implemented well. The type of research used is field research, data collection techniques through interviews and documentation, data analysis techniques, namely data analysis techniques, namely data reduction and data presentation, drawing conclusions/verification. To test the validity of the data resulting from this research, triangulation was carried out, namely by examining data from various trusted sources in various ways and at various times. There is a synergy of poverty alleviation programs that are oriented towards long-term benefits between the Tanah Datar Regency Government and the Tanah Datar Regency BAZNAS, one of which seems to be assistance in renovating the houses of mustahik or underprivileged communities. In 2023, 42 uninhabitable houses will be renovated.